Goodword islamic studies: grade 3 - Khan, Saniyasnain (Goodword books; India, 2011)
Goodword Islamic Studies: Level 3 is an engaging educational book that introduces young learners to the fundamental teachings and values of Islam through simple, age-appropriate content.